Non-invasive characterization of human bone marrow stimulation and reconstitution by cell-free messenger RNA sequencing - Arkaitz Ibarra (Nature Portfolio, 2020)
Circulating cell-free mRNA holds great promise as a non-invasive diagnostic biomarker. Here the authors show that cell-free mRNA captures transcripts from the bone marrow and can be used to non-invasively monitor dynamic changes in bone marrow physiology.